The Effect of Service Quality and Rental Prices on Customer Satisfaction at PT. Sinar Sakti Sampoerna - Rindi May Hastuti; Habbiburrahman Habbiburrahman (Journal of Management, Economic, and Accounting, 2026)
This study aims to analyze the influence of service quality and rental price on customer satisfaction at PT. Sinar Sakti Sampoerna. The main problems identified include indications of suboptimal staff service and customer perceptions regarding vehicle rental prices, which are considered relatively high. The research method employed is a quantitative approach with a causality design. The population in this study consists of all customers of PT. Sinar Sakti Sampoerna who rented vehicles during the period from January to December 2024, totaling 146 customers. Using the Slovin formula with a 10% error tolerance, a sample of 59 respondents was obtained through simple random sampling. Data were collected using questionnaires with a Likert scale and analyzed through classical assumption tests, multiple linear regression analysis, t-tests, and F-tests using SPSS 26 software.